SAT0623 CHARACTERIZING THE GUT AND PLASMA METABOLOMES IN PATIENTS WITH ANCA-ASSOCIATED VASCULITIS. (June 2019) - Najem, Catherine; Lee, Jung-Jin; Tanes, Ceylan; Strange, Cassidy; Friedman, Elliot; Sreih, Antoine; Rhee, Rennie; Geara, Abdallah; Hongzhe, LI; Bittinger, Kyle; Lewis, James; Merkel, Peter
Abstract : Background: Although a link between gut microbiome and autoimmunity has been suggested, there is a gap in the understanding of the gut metabolome in ANCA-associated vasculitis (AAV). Objectives: To explore the mechanisms by which an altered gut microbiota might predispose to ANCA-associated vasculitis (AAV), a comprehensive metabolic profiling of fecal and plasma bile acids, amino acids, and short chain fatty acids was performed in patients with AAV (granulomatosis with polyangiitis; microscopic polyangiitis; and eosinophilic granulomatosis with polyangiitis) and healthy controls. Methods: Using cross-sectional and longitudinal designs, the fecal and plasma metabolomes of patients with newly diagnosed AAV (active and in remission) were compared to chronic AAV (active and in remission), and to healthy controls. All samples were analyzed by Liquid Chromatography/Mass Spectrometry for bile acids, aminoacids, and short chain fatty acids. Gut microbiome was analyzed on the same fecal samples by sequencing the bacterial 16S rRNA gene (V1-V2 region). Association between bacterial taxa and fecal metabolites was studied using logistic regression models, correcting for multiple comparisons. Results: 78 fecal samples were studied: 37 active AAV (20 new diagnosis and 17 chronic), 25 remission, and 16 controls. 32 plasma samples were studied: 20 active AAV, 6 remission, and 6 controls. Compared to remission states, the fecal amino acids phenylalanine and tyrosine were significantly diminished in active disease. Patients with chronic AAV in remission had higher levels of plasma phenylalanine and tyrosine compared to patients with a new diagnosis of AAV in remission (p=0.02 for both). Patients with a chronic active AAV had higher levels of plasma taurolithocholic bile acid compared to patients with an active new diagnosis of AAV (Figure 1A ). Faecalibacterium was associated with this plasma bile acid (p=0.02). Plasma glycholic and glycodeoxycholic acids were strongly associated with active disease (p<0.01 and p=0.01 for both). Patients with chronic AAV in remission had higher levels of plasma taurochenodeoxycholic bile acid compared to patients with a new diagnosis of AAV in remission (Figure 1B ). Phascolarctobacterium, Sutterella, and Ruminococcus were associated with this plasma bile acid (p<0.05). Conclusion: Active AAV is associated with an altered fecal and plasma metabolome. Plasma taurochenodeoxycholic bile acid, and plasma and fecal amino acids are higher in chronic remission states compared to new diagnosis remission states, suggesting potential anti-inflammatory effects of these metabolites. Diminished metabolic diversity may be a feature of active AAV and potential biomarker to predict disease activity in AAV. References: [1] Scher J.U., et al., Microbiome in Inflammatory arthritis and human rheumatic disease. Arth Rheum, 2016. 68: p.35-45. [2] Scher J.U. Intestinal dysbiosis and potential consequences of microbiome-altering antibiotic use in the pathogenesis of human rheumatic disease. J of Rheum, 2015. 42: p.355-357. [3] Scher J.U., et al., Decreased bacterial diversity characterizes an altered gut microbiota in psoriatic arthritis and resembles dysbiosis of inflammatory bowel disease. Arth Rheum, 2015. 67(1): p.128-139 Disclosure of Interests: None declared